Student's Attitude and Semantic Knowledge Towards Learning Geometry: Basis for Learning Plan - Gimotea, Leslie Ann (Journal of Interdisciplinary Perspectives, 2024)
This research paper analyzes the difference and relationship between attitude and mathematical semantic knowledge of Grade Seven students, as a whole, and according to the profiles, namely, sex, educational attainment of the parents, family monthly income, and gadgets used for learning. The respondents of this study were restricted to seventh-grade students enrolled during the school year 2022-2023 and were selected using a random sampling technique. The study concentrates on the least mastered skills presented in the Most Essential Learning Competency of K-12 Curriculum to assess the learning gap in Geometry, where most studies need to consider a plan that could help educators teach their lessons to the varying needs and interests of the students. The data in this research were obtained using the researcher-made questionnaire that had been validated by the experts and had undergone a reliability test. The result of the study shows that female students have more positive attitudes in learning Geometry than their male counterparts. Other profiles in the study did not affect students’ attitudes toward learning Geometry. Regarding mathematical semantic knowledge, it was found that all profiles did not affect the student's performance in the geometry assessment. Moreover, students must meet the required standards in understanding and performance, requiring effective learning plans and immediate interventions to address academic gaps. The result also revealed that males performed slightly higher than females in the Geometry assessment. The Grade Seven students' attitudes significantly affect their Mathematical Semantic Knowledge only slightly. It further shows that as they become more positive towards Mathematics, their Mathematical Semantic Knowledge is more likely to increase moderately.